THE SOFT SKILLS OF HUMAN RESOURCES AND THEIR ROLE IN ENHANCING THE FOUNDATIONS OF KNOWLEDGE SHARING ))AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF INDIVIDUALS WORKING IN THE SALAH AL-DIN MUNICIPALITIES DIRECTORATE (( - Mohammed Ali Abdullah; Naji Hasan Ahmed; Ibraheem Mohammed Abd (Scholar Express Journals, 2023)
The current research seeks to demonstrate the impact of the soft skills of human resources in enhancing the foundations of knowledge sharing in the Directorate of Salah al-Din Municipalities through a case study of the opinions of a sample of its employees amounting to 60 individuals, to determine the extent of interest of their company management regarding the two research variables by adopting a questionnaire prepared for this purpose and distributed to Those interviewed, and in the light of the data collected from them, the relationships and influences between the soft skills of human resources and the foundations of knowledge sharing were tested using some statistical methods, and a set of conclusions were reached, the most prominent of which was the achievement of a correlation and a significant impact between the soft skills of human resources and the foundations of knowledge sharing in the organization Respondent and depending on the conclusions reached by the research, a set of proposals consistent with it was presented, the most prominent of which is the need for the researched organization to pay attention to the contents of management thought in the areas of human resources and knowledge sharing and deepen them among its managers and employees in a way that enhances its distinction and at the same time gives it a degree of precedence in its service fields.
Keywords: Soft Skills for Human Resources; Knowledge Sharing